2013
DOI: 10.1371/journal.pone.0063586
|View full text |Cite|
|
Sign up to set email alerts
|

A Giant Chelonioid Turtle from the Late Cretaceous of Morocco with a Suction Feeding Apparatus Unique among Tetrapods

Abstract: BackgroundSecondary adaptation to aquatic life occurred independently in several amniote lineages, including reptiles during the Mesozoic and mammals during the Cenozoic. These evolutionary shifts to aquatic environments imply major morphological modifications, especially of the feeding apparatus. Mesozoic (250–65 Myr) marine reptiles, such as ichthyosaurs, plesiosaurs, mosasaurid squamates, crocodiles, and turtles, exhibit a wide range of adaptations to aquatic feeding and a broad overlap of their tooth morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
1
36
3
1
Order By: Relevance
“…Eochelone brabantica and other related Cheloniidae were previously examined first hand for comparison with Osonachelus (Lapparent de Broin et al, 2014b), the other marine cheloniid turtle from the same latest Eocene (Priabonian) localities of Santa Cecília de Voltregà and Múnter. As it was previously demonstrated (see Bardet et al, 2013Bardet et al, , 2017Hay, 1908; Pérez-García and Lapparent de Broin, 2013; Lapparent de Broin et al, 2014a), many of the features classically identified as present in the Cheloniidae are also present in dermochelyoids (in Dermochelyidae, Protostegidae, and in a still undefined new family including Ocepechelon Bardet et al, 2013 and Alienochelys Lapparent de Broin et al, 2014a). These characteristics correspond to both plesiomorphies and/or homoplasies, often linked to the environment in which these forms lived to a feeding pattern and to the strategies of adaptation to an aquatic locomotion.…”
Section: Comparisons and Discussionsupporting
confidence: 72%
“…Eochelone brabantica and other related Cheloniidae were previously examined first hand for comparison with Osonachelus (Lapparent de Broin et al, 2014b), the other marine cheloniid turtle from the same latest Eocene (Priabonian) localities of Santa Cecília de Voltregà and Múnter. As it was previously demonstrated (see Bardet et al, 2013Bardet et al, , 2017Hay, 1908; Pérez-García and Lapparent de Broin, 2013; Lapparent de Broin et al, 2014a), many of the features classically identified as present in the Cheloniidae are also present in dermochelyoids (in Dermochelyidae, Protostegidae, and in a still undefined new family including Ocepechelon Bardet et al, 2013 and Alienochelys Lapparent de Broin et al, 2014a). These characteristics correspond to both plesiomorphies and/or homoplasies, often linked to the environment in which these forms lived to a feeding pattern and to the strategies of adaptation to an aquatic locomotion.…”
Section: Comparisons and Discussionsupporting
confidence: 72%
“…We used an updated version of the informal supertree of Foth & Joyce (2016) as the phylogenetic backbone for various statistical analyses, which differs from the published version in the position of some extinct marine turtles. In particular, pan-chelonioids were resolved according to Weems & Brown (2017) and protostegid turtles, including the 'dermochelyoids' of Bardet et al (2013) and Lapparent de Broin et al (2014), were placed as sister to thalassochelydians, as originally proposed by Joyce (2007) (but see Raselli, 2018 and for alternative phylogenetic placements for protostegids). The tree was time-calibrated in R using the package paleotree (Bapst, 2012) using information from the ages of fossils and from molecular clock studies.…”
Section: Phylogenymentioning
confidence: 91%
“…(including Ctenochelys and Toxochelys ), and dermochelyoid turtles (e.g. Ocepechelon ; Bardet et al ., ). Some Palaeogene taxa (e.g.…”
Section: Introductionmentioning
confidence: 97%